2019
DOI: 10.1002/jbm4.10240
|View full text |Cite
|
Sign up to set email alerts
|

Hip Structure Analyses in Acromegaly: Decrease of Cortical Bone Thickness After Treatment: A Longitudinal Cohort Study

Abstract: Long‐standing growth hormone (GH) excess causes the skeletal clinical signs of acromegaly with typical changes in bone geometry, including increased cortical bone thickness (CBT). However, a high prevalence and incidence of vertebral fractures has been reported. The aim of this study was to assess the course of cortical bone dimensions in the hip by comparing patients with acromegaly and clinically nonfunctioning pituitary adenomas (NFPAs) at baseline and 1 year after pituitary surgery (1‐year PO) in a longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…(2) Moreover, cortical thickness by HSA was increased in acromegaly compared with the NFPA patients and changed differently by group during 1 year of follow-up in the hip region. (20) These data were further developed in the present study. The CBT analyses were in general not dependent on sex or gonadal status in the hip region (CBT neck and CBT calcar) but lower in females in the shaft region, reflecting the women's smaller body dimensions.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…(2) Moreover, cortical thickness by HSA was increased in acromegaly compared with the NFPA patients and changed differently by group during 1 year of follow-up in the hip region. (20) These data were further developed in the present study. The CBT analyses were in general not dependent on sex or gonadal status in the hip region (CBT neck and CBT calcar) but lower in females in the shaft region, reflecting the women's smaller body dimensions.…”
Section: Discussionmentioning
confidence: 92%
“…(5,17) Based on bone mineral density (BMD) measurements of the hip (TH) and femoral neck (FN) by dual X-ray absorptiometry (DXA), structural information can be derived (hip structure analysis [HSA]) (18,19) and be of importance for understanding the biomechanical competence of the appendicular skeleton and the interplay between the different envelopes in acromegaly. (20) Whereas BMD by DXA gives a quantitative assessment of the investigated region (ex the lumbar spine [LS]), trabecular bone score (TBS) provides an estimation of bone microarchitecture, potentially reflecting the biomechanical properties of trabecular bone. (21,22) As reviewed recently, studies of TBS in acromegaly have shown inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed higher total hip and femoral neck cortical thickness and lower lumbar areal bone mineral density (BMD), trabecular bone score, and total hip trabecular volumetric BMD in patients with acromegaly than in healthy controls [ 21 ]. Another study showed an increase in femoral cortical bone thickness and an enlargement in bone diameter in patients with active acromegaly due to the prominent effect of periosteal bone formation [ 22 ]. Then, after 1 year of pituitary surgery, the femoral cortical bone thickness decreased with unchanged bone dimension, and this unbalanced geometry may consequently lead to inferior mechanical properties of the hip in patients with acromegaly [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed an increase in femoral cortical bone thickness and an enlargement in bone diameter in patients with active acromegaly due to the prominent effect of periosteal bone formation [ 22 ]. Then, after 1 year of pituitary surgery, the femoral cortical bone thickness decreased with unchanged bone dimension, and this unbalanced geometry may consequently lead to inferior mechanical properties of the hip in patients with acromegaly [ 22 ]. Additionally, after GH-lowering treatments, endocortical bone resorption becomes more prominent than periosteal bone formation, similar to normal aging, leading to decreased cortical bone thickness [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation